2009
DOI: 10.1016/s0924-9338(09)71458-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Depression and Obesity on Sleep Quality in Children/adolescents

Abstract: Aims:Limited to no literature exists on the association among sleep quality, obesity and depression in pediatric populations. This study aims to explore this association by examining the sleep quality of children and adolescents before and after a twelve-week comprehensive multidisciplinary pediatric obesity program.Methods:Archival data from the pediatric obesity program included 71 children ages 6-17 (M=10.24, SD=2.74 ) who had been assessed pre and post intervention using the Children's Depression Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Many studies have shown that there is a bidirectional association between sleep quality and anxiety symptoms, where sleep quality can be a secondary symptom to psychiatric complaints [ 32 , 33 ]. These findings are consistent with previous studies linking perceived stress with poor sleep quality among adolescents [ 34 , 35 ]. A systematic review of 9 studies suggested that there is a vicious cycle between poor sleep and many psychological disorders, with reports of reciprocal or bidirectional relationships between them [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have shown that there is a bidirectional association between sleep quality and anxiety symptoms, where sleep quality can be a secondary symptom to psychiatric complaints [ 32 , 33 ]. These findings are consistent with previous studies linking perceived stress with poor sleep quality among adolescents [ 34 , 35 ]. A systematic review of 9 studies suggested that there is a vicious cycle between poor sleep and many psychological disorders, with reports of reciprocal or bidirectional relationships between them [ 36 ].…”
Section: Discussionsupporting
confidence: 93%